2012
DOI: 10.1093/pubmed/fdr111
|View full text |Cite
|
Sign up to set email alerts
|

Multiple health behaviours: overview and implications

Abstract: We conclude that both population and high-risk strategies for health behaviour intervention are warranted, potentially synergistic and need intervention design that accounts for substitute and complementary relationships among bundled health behaviours. To maximize positive public health impact, a pressing need exists for bodies of basic and translational science that explain health behaviour bundling. Also needed is applied science that elucidates the following: (1) the optimal number of behaviours to interve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

9
269
0
11

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 314 publications
(304 citation statements)
references
References 74 publications
9
269
0
11
Order By: Relevance
“…Spring et al 4 reported that risk behaviors are more prevalent in the least favored population segments, resulting from the effects of common social determinants, including a long history of poverty and adverse environments associated with multiple unhealthy behaviors. Accordingly, the WHO 32 states that greater disease burden (e.g., infectious diseases), more lesions, and higher mortality per liter of alcohol consumed occur among individuals with lower socioeconomic status.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Spring et al 4 reported that risk behaviors are more prevalent in the least favored population segments, resulting from the effects of common social determinants, including a long history of poverty and adverse environments associated with multiple unhealthy behaviors. Accordingly, the WHO 32 states that greater disease burden (e.g., infectious diseases), more lesions, and higher mortality per liter of alcohol consumed occur among individuals with lower socioeconomic status.…”
Section: Discussionmentioning
confidence: 99%
“…The study risk behaviors -physical inactivity, tobacco smoking, experimentation of alcoholic beverages, and inadequate dietary habits -typify an unhealthy lifestyle, compromise quality of life, and predispose to the development of NCD 4,18 , and have been evaluated in various similar studies 2,[5][6][7][8][9][10][11][12][13][14][15][16][17] . However, comparison between studies that have evaluated the simultaneous occurrence of risk behaviors is complicated by the diversity of behaviors analyzed by the studies.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, we are not aware of any studies that have targeted low-income, underserved smokers known to have greater challenges with health behavior adoption. Given that supervised vigorous physical activity programs lack external validity in low-income smokers [23], there is potential utility in strategies that integrate more realistic physical activity programming (low-to-moderate intensities) within the context of smoking treatment. Such strategies may be more acceptable for this population [24], thereby also reducing attrition [25].…”
mentioning
confidence: 99%